Dialogues between the expansive logic of urbanization in Campinas/SP and the UN guidelines for sustainable cities - Lopes, André Raymundo; Sígolo, Letícia Moreira (Technical and Scientific Journal Green Cities, 2024)
This article analyzes how the urbanization process, as well as the legal framework of urban policy in Campinas-SP, relate to the Sustainable Development Goals (SDGs), the New Urban Agenda (NUA), and the guidelines of the UN's "My Neighborhood" tool for sustainable cities. Through documentary research on municipal legislation and a literature review on the concepts of compact cities, metropolitan rural areas, and also on the dispersed urbanization process of Campinas-SP, it was possible to identify guidelines present in the legal framework of the city's urban policy that support dispersed urban growth to the detriment of environmental preservation and the consolidation of a metropolitan rural landscape, contradicting the UN's sustainable goals. The research resulted in comparative charts between the guidelines present in the 2018 Campinas-SP Master Plan and the UN documents and tools for sustainable cities analyzed, concluding that the contradictions within the municipality's legal framework hinder the consolidation of a more compact city that contains urban expansion, preserves the environment, and consolidates the metropolitan rural landscape. The analysis highlights the importance of drafting urban legislation in Campinas-SP, beyond the Master Plan, that aligns with the sustainable development goals.
Keywords: compact city; dispersed urbanization; Sustainable Development Goals